Consumer perception and adoption of a circular chemical economy - Kaiwen Chang; Ruini Qu; Umit Bititci; Jin Xuan; Bing Xu (Cleaner and Responsible Consumption)
This study highlights the critical role of consumer behaviour in advancing the UK's transition to a Circular Chemical Economy (CCE), a sector heavily reliant on fossil fuels and a major contributor to CO2 emissions. While most existing studies focus on the technological and economic viability of a CCE, we explore the less examined dimension of consumer perceptions and behavioural responses to circular products and recycling practices. By leveraging the Theory of Planned Behaviour (TPB), we analyse unique survey data from 2,418 UK participants. The findings reveal that consumer attitude, and societal impact significantly influence consumers' willingness to pay (WTP) for circular products, while perceived behavioural control emerges as the most influential factor in their willingness to recycle (WTR). These insights are vital for policymakers and industry stakeholders aiming to stimulate behavioural change. The study offers several recommendations, including enhancing awareness and understanding of CCE products and recycling practices, fostering collaboration and partnerships, promoting the use of clear and standardised labelling, and designing effective incentives. Although our results are based on extensive UK-based data, they offer valuable insights for countries with similar socio-economic characteristics.